Colitis induced in mice with dextran sulfate sodium (DSS) is mediated by the NLRP3 inflammasome. Issue 9 (4th May 2010) - Bauer, Christian; Duewell, Peter; Mayer, Christine; Lehr, Hans Anton; Fitzgerald, Katherine A; Dauer, Marc; Tschopp, Jurg; Endres, Stefan; Latz, Eicke; Schnurr, Max
Abstract : Background: The proinflammatory cytokines interleukin 1β (IL-1β) and IL-18 are central players in the pathogenesis of inflammatory bowel disease (IBD). In response to a variety of microbial components and crystalline substances, both cytokines are processed via the caspase-1-activating multiprotein complex, the NLRP3 inflammasome. Here, the role of the NLRP3 inflammasome in experimental colitis induced by dextran sodium sulfate (DSS) was examined. Methods: IL-1β production in response to DSS was studied in macrophages of wild-type, caspase-1 −/−, NLRP3 −/−, ASC −/−, cathepsin B −/− or cathepsin L −/− mice. Colitis was induced in C57BL/6 and NLRP3 −/− mice by oral DSS administration. A clinical disease activity score was evaluated daily. Histological colitis severity and expression of cytokines were determined in colonic tissue. Results: Macrophages incubated with DSS in vitro secreted high levels of IL-1β in a caspase-1-dependent manner. IL-1β secretion was abrogated in macrophages lacking NLRP3, ASC or caspase-1, indicating that DSS activates caspase-1 via the NLRP3 inflammasome. Moreover, IL-1β secretion was dependent on phagocytosis, lysosomal maturation, cathepsin B and L, and reactive oxygen species (ROS). After oral administration of DSS, NLRP3 −/− mice developed a less severe colitis than wild-type mice and produced lower levels of proinflammatory cytokines in colonic tissue. Pharmacological inhibition of caspase-1 with pralnacasan achieved a level of mucosal protection comparable with NLRP3 deficiency. Conclusions: The NLRP3 inflammasome was identified as a critical mechanism of intestinal inflammation in the DSS colitis model. The NLRP3 inflammasome may serve as a potential target for the development of novel therapeutics for patients with IBD.